2017
DOI: 10.1002/app.44998
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antibacterial cellulose with s‐triazine‐based quaternarized N‐halamine

Abstract: To reduce the neutral salt used in the textile finishing with s‐triazine derivatives, a novel s‐triazine‐based quaternarized N‐halamine precursor was synthesized by two simple steps and characterized by H‐NMR and FT‐IR. This compound can be effectively coated onto cellulose by nucleophilic substitution process without neutral salt. The treated cellulose was rendered with powerful biocidal efficacy after transferring to an N‐halamine structure by exposing to dilute sodium hypochlorite solution through the syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Owing to their long-term stability in aqueous and dry storage conditions, regenerability, nontoxicity, low cost, and highly efficient broad-spectrum activity against bacteria, viruses, fungi, and yeasts, N-halamines have found various applications in water treatment, food packaging, latex paint, household sanitations, and air cleaning materials [142][143][144][145][146]. Cellulose is a suitable candidate to be functionalized with N-halamines due to abundance of hydroxyl groups on its backbone which can be easily grafted with N-halamine [147]. Various N-halamine precursors with reactive agents including epoxy groups and organosiloxane have been grafted onto cellulose, and durable antibacterial compounds have been developed.…”
Section: Quaternized Halaminementioning
confidence: 99%
“…Owing to their long-term stability in aqueous and dry storage conditions, regenerability, nontoxicity, low cost, and highly efficient broad-spectrum activity against bacteria, viruses, fungi, and yeasts, N-halamines have found various applications in water treatment, food packaging, latex paint, household sanitations, and air cleaning materials [142][143][144][145][146]. Cellulose is a suitable candidate to be functionalized with N-halamines due to abundance of hydroxyl groups on its backbone which can be easily grafted with N-halamine [147]. Various N-halamine precursors with reactive agents including epoxy groups and organosiloxane have been grafted onto cellulose, and durable antibacterial compounds have been developed.…”
Section: Quaternized Halaminementioning
confidence: 99%
“…11,12 So, the modifications of GF and the interface between GF and polymer matrix were investigated in many reports. For example, Li et al 13 reported that the introduction of amino-terminated hyperbranched polymer into the polymer matrix can improve the interface between GF and polymer matrix; Chen et al 7 reported that the [(6-oxido-6H-dibenz [c,e] [1,2] oxaphosphorin-6-yl)-methyl]-butanedioic acid also can strengthen the interfacial adhesion between GF and the resin matrix; other modified GF coated with titanate coupler and rare earths were reported by Jiang et al 14 and Cheng et al, 15 respectively. The methods aforementioned to enhance the interfacial adhesion between GF and polymer matrix can contribute to the mechanical properties to some extent, but the methods also exhibit the disadvantages such as increasing the cost, reducing the thermal stability and complex modification operation, and in particularly, may limit the curing temperatures due to the thermal instability of the modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the activation energy indicates that the reaction components require more energy to complete the reaction. 32 As shown in Fig. 9(b), with an increase in the value of , the value of E a has a relatively small fluctuation in the early stage.…”
Section: Curing Behaviormentioning
confidence: 80%
“…The basic assumption for the application of the DSC technique to the cure of modified epoxy resins is that the rate of the kinetic process is proportional to the measured heat flow. 30,32 Figure 7 shows the DSC thermograms at various heating rates. The percentage conversion as a function of temperature at various heating rates as calculated from the DSC data is shown in Fig.…”
Section: Curing Behaviormentioning
confidence: 99%